Tradisi Barikan Masyarakat Nahdliyin Dalam Perspektif Talcott Parsons - 'Aydi, Ulil; Fahrurrosin, Fahrurrosin (Journal of Nahdlatul Ulama Studies, 2023)
The Barikan tradition in Jungpasir Village, Wedung District, Demak Regency is a cultural expression that functions as a form of gratitude and hope for safety and blessings in agriculture. This study aims to analyze the role of the Barikan tradition in the social structure of society using the AGIL Talcott Parsons approach. The results of the study indicate that Barikan not only has ritual value, but also becomes an instrument in strengthening social cohesion and maintaining the balance of culture and customary law. From the aspect of adaptation, this tradition is a community strategy in dealing with agricultural uncertainty. The achievement of goals is reflected in efforts to preserve ancestral heritage values. The integration function is seen from the acculturation between Islamic teachings and local culture which strengthens social solidarity, while latency plays a role in reproducing social values between generations. These findings indicate that the Barikan tradition is not only maintained because of its spiritual elements, but also because of its significance in maintaining the social and economic structure of society. This study contributes to the understanding of the interaction between law, culture, and religion in shaping sustainable social practices.